MAKNA LITERASI KEUANGAN DIGITAL BAGI PENGELOLA KEUANGAN SEKOLAH: KAJIAN ETNOGRAFI PADA ERA DIGITALISASI PENDIDIKAN - Eko Cahyadi; Supatmin Supatmin; Dina Novita (Jurnal Manajemen & Pendidikan [JUMANDIK], 2026)
This study examines the meaning of digital financial literacy for school financial managers in Indonesia amid the ongoing massive digital transformation of the education sector. Despite government efforts to promote digital transformation in education through various regulations and programs, an in-depth understanding of how school financial managers—treasurers and administrative heads—interpret, internalize, and practice digital financial literacy in their daily work routines remains scarce. This study employed an ethnographic approach over nine months across six public junior and senior high schools in DKI Jakarta and West Java provinces, collecting data through participant observation, in-depth interviews with 18 informants, and analysis of school financial documents. Findings reveal that the meaning of digital financial literacy for school financial managers is polysemic: it is simultaneously perceived as a tool of administrative compliance, a source of technological anxiety, a medium of professional empowerment, and an arena for occupational identity negotiation. This research contributes to the development of a contextually grounded financial literacy framework responsive to the realities of Indonesian public educational institutions, while offering empirically-based policy recommendations for capacity-building programs targeting school financial managers.